Severe disseminated tuberculosis in HIV-negative refugees - Suárez, Isabelle; Maria Fünger, Sarah; Jung, Norma; Lehmann, Clara; Reimer, Robert Peter; Mehrkens, Dennis; Bunte, Anne; Plum, Georg; Jaspers, Natalie; Schmidt, Matthias; Fätkenheuer, Gerd; Rybniker, Jan (The Lancet infectious diseases, 2019)
In high-income countries, the presentation of tuberculosis is changing, primarily because of migration, and understanding the specific health needs of susceptible populations is becoming increasingly important. Although disseminated tuberculosis is well documented in HIV-positive patients, the disease is poorly described and less expected in HIV-negative individuals. In this Grand Round, we report eight HIV-negative refugees, who presented with extensively disseminated tuberculosis. We discuss the multifactorial causes, such as deprivations during long journeys, precarious living conditions, and the experience of violence, which might add to nutritional factors and chronic disorders, eventually resulting in a state of predisposition to immune deficiency. We also show that disseminated tuberculosis is often difficult to diagnose when pulmonary symptoms are absent. Communication difficulties between refugees and health-care workers are another major hurdle, and every effort should be made to get a valid patient history. This medical history is crucial to guide imaging and other diagnostic procedures to establish a definite diagnosis, which should be confirmed by a positive tuberculosis culture. Because many of these patients are at risk for multidrug-resistant tuberculosis, drug susceptibility testing is imperative to guide therapy. In the absence of treatment guidelines for this entity, clinicians can determine treatment duration according to recommendations provided for extrapulmonary tuberculosis and affected organs. Paradoxical expansion of tuberculous lesions during therapy should be treated with corticosteroids. In many cases, treatment duration must be individualised and might even exceed 12 months.